Estudo morfométrico da aorta de pacientes autopsiados com hipertensão arterial sistêmica - JULIANO, Gabriela Ribeiro (2018)
Introduction: Systemic arterial hypertension (SAH) is characterized as a multifactorial disease and is characterized by the presence of elevated blood pressure levels. It is also related to functional and/or structural alterations of target organs, as well as in endothelium, elasticity and arterial thickening. The objective of this study was to evaluate the intensity of macroscopically and microscopically atherosclerosis, the percentage of elastic fibers, collagen fibers and lipid deposits in the intima and middle layers of the aortas of autopsied patients with and without SAH according to age, sex, ethnicity and body mass index (BMI). Methods: We collected 52 fragments of the aorta from autopsied patients and divided into two groups, 26 with SAH and 26 without SAH. The intensity of atherosclerosis was quantitatively assessed in macroscopy and microscopy in semiquantitative form. The histopathological process of the slides and the quantification of elastic, collagen and lipid deposit percentage, being correlated with age and BMI and compared with sex and ethnicity, the Leica Qwin Plus® image analyzer system was used. Results: The group with hypertension had a higher macroscopic intensity of atherosclerosis, a lower percentage of elastic fibers, a higher percentage of collagen fibers and a lipid deposit. In the macroscopic intensity of atherosclerosis there was an increase with age in patients autopsied with SAH and without SAH. Regarding sex, in women there was a higher percentage of lipid deposition with SAH and without SAH. Conclusion: The SAH was related to the accumulation of lipid deposits in the aorta artery and was noted as a preponderant risk factor for the advancement of atherosclerosis. The advancement of age and the female sex has been shown to be a condition for the marked development of the lipid deposit.